Language, identities and ideologies of the past and present Chukotka - Morgounova, Daria (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2007)
AbstractThe historical background of Chukotka is one of intensive language contact and of rapid socio-political, economic, cultural and spiritual change, which often makes any predictions difficult, also in regard to language. When I first came to Chukotka in 2003, the Yupiget sense of ethnic awareness was very strong. The majority of the Yupik population expressed positive attitudes towards their Native language and seemed to be supportive of its revitalisation. However, when I returned to Chukotka in 2005, I found out that the Yupik language status and loyalty had shifted. In this paper, I discuss language shift in Chukotka with reference to St. Lawrence Island, Alaska. I also cast light on language transformations and adaptation that I have documented during my fieldwork in the area in 2003 and 2005, and give possible explanations as to why the revitalisation movement that I witnessed in the beginning of the new millennium was short-lived and had ceased by 2005.